Cognitive disorders at essential arterial hypertension (review of literature) - V. M. Polyakov (Acta Biomedica Scientifica, 2013)
The review is devoted to the analysis of cognitive disorders in patients with essential arterial hypertension. (EAH). Some brain disorders that cause the formation of cognitive defect at arterial hypertension are described. There are some data about peculiarities of cognitive disorders in children and. adolescents with EAH. In some articles EAH is considered as a risk factor for disorders of memory and. other cognitive functions, especially in middle-aged and. elderly people, and. there is statistically significant negative connection between the levels of systolic and. diastolic blood pressure and. indices of cognitive disorders. The development of leucoariosis is often the basis of these disorders at arterial hypertension, that causes formation of syndrome of disconnection between cerebral cortex and. basal ganglions. It is accompanied by the decrease of attention concentration, increased wasting of psychic processes, memory disorders, emotional and behavioral disorders. The most typical syndrome in this case at subcortical brain lesions in patients with EAH is decrease of memory with progressive mnestic defect. Method of one-photon emission tomography in patients with hypertension encephalopathy showed decrease of perfusion of focal character in the projection of temporal lobes of brain in 87,8 % of examined. patients. Hypoperfusion in left temporal lobe was accompanied by the decrease of aural-vocal memory. Cognitive disorders (voluntary attention, short- and. long-term memory and. also worsening of mathematical and creative possibilities) were already registered at the stages of EAH formation in adolescent age. In this age also functional insufficiency of diencephalic formations in brain, disorders of cortical-subcortical connections, presence of signs of decelerating of functional maturing of interhemispheric interrelations and. frontal lobe of brain were found. Thus on the basis of literary data we can suppose that EAH is independent factor of risk of development of cognitive dysfunction in all age groups.